Pengaruh Penambahan Ca(NO3)2 Terhadap Hasil Tanaman Selada Kriting (Lactuca Sativa L.) pada Sistem Hidroponik Deep Flow Technique (DFT) - SURYANTINI, NI NYOMAN; WIJANA, GEDE; DWIYANI, RINDANG (Agrotrop : Journal on Agriculture Science, 2020)
The Effect of Addition of Ca(NO 3 ) 2 to the Results of Lettuce ( Lactuca sativa L.) in the Hydroponic System of Deep Flow Technique (DFT) . Plants, in general, require composition, concentration, and volume of nutrient solutions which different depends on the type and phase of plant growth. Leaf vegetable crops such as lettuce ( Lactuca sativa L.) require higher Nitrogen (N) nutrients than other vegetable crops, but the problem we faced at the moment is the hydroponic nutrients that are traded only in the general form of nutrient, therefore the addition of N nutrients in the form of calcium nitrate (Ca(NO 3 ) 2 ) needs to be done to meet the needs of lettuce plants. This study was aimed to determine the effect of the addition of Ca(NO 3 ) 2 and to find the optimum dosage of the addition of Ca(NO 3 ) 2 to the general hydroponic nutrition of vegetables on lettuce use DFT hydroponic system. The treatments consisted of five levels which are nutrition AB Mix general vegetable as a control, and nutrition AB Mix with the addition of 30 g, 60 g, 90 g, and 120 g Ca(NO 3 ) 2 .  The results of the observation showed that the treatment of the addition of Ca(NO 3 ) 2 fertilizer had a very significant effect on all observed variables, except for the diameter of the lettuce plant. The optimum addition of Ca(NO 3 ) 2 for lettuce was found at 90.04 g with a maximum yield of 207.92 g.